Mining Genes Related to Single Fruit Weight of Peach (Prunus persica) Based on WGCNA and GSEA - Hangling Bie; Huimin Wang; Lirong Wang; Yong Li; Weichao Fang; Changwen Chen; Xinwei Wang; Jinlong Wu; Ke Cao (Horticulturae, 2023)
Single fruit weight is an important goal of crop production and horticultural species domestication, but its genetic mechanism is still unclear. In this study, the fruits of different peach fruit types in their first rapid development period were used as materials. First, the differentially expressed genes were analyzed by RNA-seq data. Secondly, weighted gene co-expression network analysis (WGCNA) was used to calculate the correlation between genes and modules, the genes with different expression patterns were divided into 17 modules, the modules were correlated with the phenotype of single fruit, and a highly correlated blue module was obtained. Then, the possible differentially expressed genes and signal pathways among different fruit types were compared by gene set enrichment analysis (GSEA) and 43 significant pathways were obtained. Finally, 54 genes found to be repeatedly expressed in 3 of the methods were screened, and 11 genes involved in plant hormone signal transduction were selected for subsequent analysis according to their functional annotations. Combined with the changing trend of phenotype, three genes (Prupe.7G234800, Prupe.8G079200 and Prupe.8G082100) were obtained as candidate genes for single fruit weight traits. All three genes are involved in auxin signal transduction, with auxin playing an important role in plant growth and development. This discovery provides a new perspective for revealing the genetic law of single fruit weight in peach.